2003
DOI: 10.1108/13673270310505377
|View full text |Cite
|
Sign up to set email alerts
|

Developing a measure of knowledge management behaviors and practices

Abstract: Knowledge management has recently emerged as a new discipline and is generating considerable interest among academics and managers. Given its newness, there is still little guidance in the extant literature on how to measure knowledge management. This paper presents the ®rst scale developed to measure knowledge management behaviors and practices and in so doing provides construct boundaries that should enable the development of a theory of knowledge management (Zaltman et al., 1973).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
291
0
29

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(333 citation statements)
references
References 38 publications
13
291
0
29
Order By: Relevance
“…However, reports of successful outcomes from KM initiatives are far from being seen as the norm (see section 1.6, for instance). The ambiguity over success or failure raises a number of questions and points: for instance, the perceived limited availability of valid methods and tools of measurement, although there are some exceptions (e.g., Chourides, Longbottom and Murphy, 2003;and Ragab and Arisha, 2013;Darroch, 2003).…”
Section: Exploring Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reports of successful outcomes from KM initiatives are far from being seen as the norm (see section 1.6, for instance). The ambiguity over success or failure raises a number of questions and points: for instance, the perceived limited availability of valid methods and tools of measurement, although there are some exceptions (e.g., Chourides, Longbottom and Murphy, 2003;and Ragab and Arisha, 2013;Darroch, 2003).…”
Section: Exploring Implicationsmentioning
confidence: 99%
“…Jenny Darroch (2003) claims to be the first to develop a scale to measure KM behaviours and practices which she suggests will help in the development of a theory of KM. The scale is specifically developed to measure behaviours in knowledge acquisition, dissemination and responsiveness (use of knowledge), and underwent a (claimed) rigorous development and validity testing program.…”
Section: Measuring Knowledge Managementmentioning
confidence: 99%
“…Yang reported that the knowledge management strategyperformance connection was contingent on both performance-driven strategies, including reward system and process innovation and knowledge management-based competencies. Darroch (2003) presented a scale developed to measure knowledge management behaviors and practices. Lee and Choi (2003) studied knowledge management enablers, processes, and organizational performance by developing a framework, which interconnects knowledge management factors.…”
Section: 1knowledge Management and Its Significantmentioning
confidence: 99%
“…Some view KM as the management of processes that enable the movement of knowledge into, through and out of the organization with the ultimate aim of enhancing organizational efficiency and performance (Firestone & McEllroy, 2005;Darroch, 2003). Fatt et al (2010) view KM as "a tool by which the organization's core competencies can be focused and developed".…”
Section: Introductionmentioning
confidence: 99%